Proposta de método para análise do retorno sobre investimentos em qualidade de software - Birolo, Aline Bez (Universidade do Vale do Rio dos Sinos, 2017)
The information technology market has undergone a major revolution in recent years due to the increase in software requirements, which began to emerge when the use of computers became essential in the administration of organizations and even in the People's lives. Faced with this scenario, software developers have invested heavily in improvements in processes to ensure higher quality in their products. Financial pressure to remain stable in the market requires clear demonstrations of returns in order to justify investments. This paper proposes a method to analyze return on investments in Software Quality, through a case study. The main findings showed that analyzing return on investments develops a series of competencies in the organization, such as assertiveness in the decision-making process, greater financial stability and a results-oriented culture.
Keywords: Tecnologia da Informação; Administração das organizações; Investimentos; Information technology; Investments; Administration of organizations